2011
DOI: 10.1152/ajpregu.00556.2010
|View full text |Cite
|
Sign up to set email alerts
|

Hindbrain noradrenergic A2 neurons: diverse roles in autonomic, endocrine, cognitive, and behavioral functions

Abstract: Central noradrenergic (NA) signaling is broadly implicated in behavioral and physiological processes related to attention, arousal, motivation, learning and memory, and homeostasis. This review focuses on the A2 cell group of NA neurons, located within the hindbrain dorsal vagal complex (DVC). The intra-DVC location of A2 neurons supports their role in vagal sensory-motor reflex arcs and visceral motor outflow. A2 neurons also are reciprocally connected with multiple brain stem, hypothalamic, and limbic forebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
220
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(232 citation statements)
references
References 277 publications
(173 reference statements)
12
220
0
Order By: Relevance
“…Because A2 neurons are strongly implicated in satiety mechanisms (reviewed in Ref. 45), including those that survive decerebration (25), an alternative hypothesis to an orexigenic (excitatory) role for NPY on prehypoglossal neurons could involve the colocalization of NPY in a subset of A2 neurons (19,48). In that case, the inhibition of preoromotor neurons observed in the present study could represent a brain stem satiety pathway originating from A2 neurons in the cNST, in which the release of NPY and/or NE suppresses excitatory …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because A2 neurons are strongly implicated in satiety mechanisms (reviewed in Ref. 45), including those that survive decerebration (25), an alternative hypothesis to an orexigenic (excitatory) role for NPY on prehypoglossal neurons could involve the colocalization of NPY in a subset of A2 neurons (19,48). In that case, the inhibition of preoromotor neurons observed in the present study could represent a brain stem satiety pathway originating from A2 neurons in the cNST, in which the release of NPY and/or NE suppresses excitatory …”
Section: Discussionmentioning
confidence: 99%
“…Results from decerebrate preparations in which visceral signals, such as gastric load (49) and glucoprivation (15, 21), modify the amount of a palatable (sweet) stimulus that is consumed, suggest that these local pathways exert a potent influence over this consummatory circuitry (reviewed in Refs. 24,45,46). Although some amino acid-mediated excitatory and inhibitory inputs to IRt/PCRt preoromotor neurons have been identified from the rostral (gustatory) nucleus of the solitary tract (41), little is known of the neurochemical identity of other local modulatory influences on these neurons.…”
mentioning
confidence: 99%
“…In the cNST, MOR activation suppresses ST input to A2 (Cui et al 2012) and POMC (Appleyard et al 2005) neurons, effects also compatible with an orexigenic influence since these neuronal populations have been implicated in satiety (Rinaman 2011). Although early reports suggested that rNST DAMGO infusions also increased food intake (Kotz et al 1997), these studies used rather large infusions and the feeding effect was delayed, suggesting that the orexigenic effect may have arisen from ligand spread that suppressed satiety signals in cNST (Kinzeler and Travers 2011).…”
Section: Damgo (Presynaptically) Suppresses St-evoked Responses In Thmentioning
confidence: 97%
“…Noradrenaline transmission has different effects. Noradrenaline increases in PVH at the onset of the periods of food intake and stimulates carbohydrate intake through binding to α2 receptors (Alexander, Cheung, Dietz, & Leibowitz, 1993); however, noradrenaline in the NTS-PVH pathway is also a principal mediator of several satiation stimuli (Rinaman, 2011).…”
Section: Homeostatic Systemmentioning
confidence: 99%